2022
DOI: 10.1155/2022/9565320
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Patient Satisfaction with Complete Dentures

Abstract: Background. Rehabilitation of the edentulous patients has always been a challenge. The success of conventional complete denture therapy might be affected by several factors such as patients’ age, personality, previous denture wearing experience, expectations, aesthetics, residual ridge form and anatomy, denture quality, the method of its construction, dentist experience, and dentist-patient relations. Objectives. The aim of this study was to compare patient satisfaction with complete dentures provided by fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
(26 reference statements)
4
14
0
1
Order By: Relevance
“…In the present study putting hands on the difference in patient's satisfaction with different levels of operator's experience, was evaluated. The results indicated that for many reasons, no significant difference was observed in patient satisfaction and quality of life with the complete dentures constructed by dental students and those by professional prosthodontists, and that conclusion was in accordance with other research (28,29,31) .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the present study putting hands on the difference in patient's satisfaction with different levels of operator's experience, was evaluated. The results indicated that for many reasons, no significant difference was observed in patient satisfaction and quality of life with the complete dentures constructed by dental students and those by professional prosthodontists, and that conclusion was in accordance with other research (28,29,31) .…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with this study's results, a study stated that the high-quality complete dentures provided by experienced dentists may not lead to good patient satisfaction; therefore, it is difficult to evaluate the significance of experience in the denture treatment field (28) . Some authors' results supporting this study, also found no significant correlation between the dentists' experience and patients' satisfaction with their complete dentures (28,32) , which is the same conclusion of the present study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations